(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Background:. Deep vein thrombosis and pulmonary embolism are rare complications of uterine myoma. There have been few reports on these associations. Case: A 41 year old para 1+0 presented with 20 weeks size fibroid uterus, which had compressed the pelvic veins and caused unilateral deep vein thrombosis of right leg with subsequent pulmonary embolism. After anticoagulation therapy, a total abdominal hysterectomy was performed, with an uneventful recovery. Conclusion: Although deep vein thrombosis and pulmonary embolism associated with uterine myoma is a rare event, it can be managed successfully with anticoagulants and hysterectomy. A uterine myoma with deep vein thrombosis and pulmonary embolism is an indication for hysterectomy. DOI: 10.3329/bjog.v23i2.4965 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(2) : 78-81